Uncovering Candidate Genes Controlling Major Fruit-Related Traits in Pepper via Genotype-by-Sequencing Based QTL Mapping and Genome-Wide Association Study - Lee, Hea-Young; Ro, Na-Young; Patil, Abhinandan; Lee, Joung-Ho; Kwon, Jin-Kyung; Kang, Byoung-Cheorl (Frontiers in Plant Science, 2020)
All modern pepper accessions are products of the domestication of wild Capsicum species. However, due to the limited availability of genome-wide association study (GWAS) data and selection signatures for various traits, domestication-related genes have not been identified in pepper. Here, to address this problem, we obtained data for major fruit-related domestication traits (fruit length, width, weight, pericarp thickness, and fruit position) using a highly diverse panel of 351 pepper accessions representing the worldwide Capsicum germplasm. Using a genotype-by-sequencing (GBS) method, we developed 187,966 genome-wide high-quality SNP markers across 230 C. annuum accessions. Linkage disequilibrium (LD) analysis revealed that the average length of the LD blocks was 149 kb. Using GWAS, we identified 111 genes that were linked to 64 significant LD blocks. We cross-validated the GWAS results using 17 fruit-related QTLs and identified 16 causal genes thought to be associated with fruit morphology-related domestication traits, with molecular functions such as cell division and expansion. The significant LD blocks and candidate genes identified in this study provide unique molecular footprints for deciphering the domestication history of Capsicum. Further functional validation of these candidate genes should accelerate the cloning of genes for major fruit-related traits in pepper.